Seni Ukir Kayu Balairung Koto Piliang Nagari Paninggahan Kabupaten Solok Sumatera Barat - Sri Depi Handayani; Purwo Prihatin (Universitas PGRI Palembang, 2023)
This research aims to determine the art of carving applied to the Koto Piliang Nagari Paninggahan hall, Solok Regency, West Sumatra. The problem is focused on the sculptural art that is applied to the balairung which takes the idea of nature takambang being a teacher, which comes from the motif of the names of plants, animals and the names of other natural objects. In order to approach this problem, Fielman's aesthetic theory was used with qualitative research methods. The data were collected through field studies, literature studies, interviews as well as documentation and comprehensive data analysis. This study concludes that the sculptural art applied to the balairung has an aesthetic value that describes the harmony and harmony of people's lives in Minangkabau and has a kinship life system, togetherness in the governance system in Minangkabau society. Keywords: Carving Art; Balairung Koto Piliang; Peninggahan, Solok Regency